Attitude and emotions of young Portuguese tourists toward international risk destinations. - Ambrósio, V.; Loureiro, S. (Conference Book Proceedings 8th EuroMed Conference of the EuroMed Academy of Business, 2015)
The main goals of this ongoing study are to learn about attitude of young Portuguese tourists about risk destinations and their emotions about traveling out of the country.